Respiratory and Gut Microbiome Modification during Respiratory Syncytial Virus Infection: A Systematic Review - Kazuma Yagi; Nicholas W. Lukacs; Gary B. Huffnagle; Hideo Kato; Nobuhiro Asai (Viruses, 2024)
Background: Respiratory syncytial virus (RSV) infection is a major cause of lower respiratory tract infection, especially in infants, and increases the risk of recurrent wheezing and asthma. Recently, researchers have proposed a possible association between respiratory diseases and microbiome alterations. However, this connection has not been fully established. Herein, we conducted a systematic literature review to evaluate the reported evidence of microbiome alterations in patients with RSV infection. Methods: The systematic literature review on the association between RSV and microbiome in humans was conducted by searching PubMed, EMBASE, Scopus, and CINAHL from 2012 until February 2022. The results were analyzed qualitatively, focusing on the relationship between microbiome and RSV infection with available key microbiome-related parameters. Results: In the 405 articles identified by searching databases, 12 (Respiratory tract: 9, Gut: 2, Both: 1) articles in line with the research aims were eligible for this qualitative review. The types of samples for the respiratory tract microbiome and the sequencing methods utilized varied from study to study. This review revealed that the overall microbial composition in both the respiratory tract and gut in RSV-infected patients was different from that in healthy controls. Our generated results demonstrated an increase in the abundance of Haemophilus and Streptococcus, which could contribute to the distinctive separation based on the beta diversity in the respiratory tract. Conclusions: The respiratory tract and gut microbiome changed in patients with RSV infection. Further research with a well-organized longitudinal design is warranted to clarify the impact of microbiome alterations on disease pathogenesis.